2013
DOI: 10.1080/02699931.2013.853648
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in managing response to sadness elicitors using attentional deployment, positive reappraisal and suppression

Abstract: The current study investigated age differences in the use of attentional deployment, positive reappraisal, and suppression while regulating responses to sadness-eliciting content. We also tested to what extent these emotion regulation strategies were useful for each age group in managing response to age-relevant sad information. Forty-two young participants (Mage = 18.5, SE = .15) and 48 older participants (Mage = 71.42, SE = 1.15) watched four sadness-eliciting videos (about death/illness, 4–5 minutes long) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
138
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 64 publications
18
138
4
2
Order By: Relevance
“…Some studies show no age differences in the effective suppression of negative experience [2022], while others suggest age-related improvements in the suppression of negative emotional experience [2324]. Of note, studies that fail to observe age differences in emotion suppression assess participants’ expression of negative emotions, not subjective experience of emotions.…”
Section: Studies Of Emotion Regulation Across the Life Spanmentioning
confidence: 99%
“…Some studies show no age differences in the effective suppression of negative experience [2022], while others suggest age-related improvements in the suppression of negative emotional experience [2324]. Of note, studies that fail to observe age differences in emotion suppression assess participants’ expression of negative emotions, not subjective experience of emotions.…”
Section: Studies Of Emotion Regulation Across the Life Spanmentioning
confidence: 99%
“…The latest cross-sectional studies in this field have found that the capacity for emotion regulation improves with age (Scheibe & Carstensen, 2010); in other words, as they grow older, people are better able to avoid negative emotions. Furthermore, a trend has also been observed which indicates that regulation capacity evolves from an instrumental or environmental strategy towards a more internal type of regulation (Blanchard-Fields, Stein, & Watson, 2004;Lohani & Isaacowitz, 2014). The emotion regulation model proposed by John (1997, 2002) argues that diverse emotion regulation strategies are used by the same individual throughout the course of their emotional response.…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, older adults appear to be less effective when using detached reappraisal (Shiota & Levenson, 2009) and suppression ability seems to be maintained (Lohani & Isaacowitz, 2014). If older adults use more effective strategies and are more effective when using their preferred strategies, they may be more effective interpersonal regulators compared to younger adults.…”
Section: Emotion Regulation Effectivenessmentioning
confidence: 99%
“…Additionally, the use of certain strategies appears to get better with age. Older adults are more effective when using attentional deployment (Lohani & Isaacowitz, 2014) and specifically positive reappraisal (Lohani & Isaacowitz, 2014;Shiota & Levenson, 2009). …”
Section: Emotion Regulation Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation